A new boundary growth model for the analysis of microscopic blockage and various cross-section shapes effects in porous functional medical material - Hao, Junhong; Wu, Xuefeng; Ma, Tengyu; Ju, Chenzhi; Hao, Tong; Li, Wenchao (Frontiers in Materials, 2024)
The simulation of physical processes in functional medical materials plays an important role in the characterization of their properties. In this paper, the boundary growth factor for blood coagulation in functional hemostatic materials is proposed for the first time, a physical model for the evolution of microscopic obstruction of blood coagulation in functional hemostatic materials is constructed, and the accuracy of the model is verified. And through CFD, it focused on analyzing the effects of different inlet pressures, external temperatures and material shape factors on the hemostatic performance of functional hemostatic materials, using the flow cut-off time of blood as the metric. The results show that: as blood flows into the material, thrombus begins to form at the boundary and progresses toward the center; smaller inlet pressures promote thrombus growth; external temperature has little effect on thrombus growth; materials possessing smaller flow rates beneficial to thrombus growth; and the larger the crosssectional area in the material's flow channel, the faster blood coagulates.